2020
DOI: 10.20944/preprints202004.0058.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Was School Closure Effective in Mitigating Coronavirus Disease 2019 (COVID-19)? Time Series Analysis Using Bayesian Inference

Abstract: Background: Coronavirus disease 2019 (COVID-19) pandemic are causing significant damages to many nations. For mitigating its risk, Japan’s Prime Minister called on all elementary, junior high and high schools nationwide to close beginning March 1, 2020. However, its effectiveness in decreasing disease burden has not been investigated. Methods: We used daily data on the report of COVID-19 and coronavirus infection incidence in Japan until March 31, 2020. Time series analysis were conducted using Bayes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(56 citation statements)
references
References 5 publications
0
56
0
Order By: Relevance
“…Lawanto et al, 2014, found higher performing students accessed course content significantly more than lower performers, illustrating that engagement and goal setting is vital for online learning. Further research should be conducted on the effectiveness of school closings for diminishing the spread of COVID-19, as has been found to be minimal in Japan (Iwata et al, 2020). The results of this study are limited to the initial outbreak and reflect opinions of students having to re-adjust their remaining semester to exclusive online learning, and are likely biased, given the short amount of time students were given to prepare for distance learning.…”
Section: Resultsmentioning
confidence: 92%
“…Lawanto et al, 2014, found higher performing students accessed course content significantly more than lower performers, illustrating that engagement and goal setting is vital for online learning. Further research should be conducted on the effectiveness of school closings for diminishing the spread of COVID-19, as has been found to be minimal in Japan (Iwata et al, 2020). The results of this study are limited to the initial outbreak and reflect opinions of students having to re-adjust their remaining semester to exclusive online learning, and are likely biased, given the short amount of time students were given to prepare for distance learning.…”
Section: Resultsmentioning
confidence: 92%
“…Included studies are described in Table 1. All studies [13][14][15][16][17][18][19][20][21][22] reported the effect of school closures on community transmission of SARS-CoV-2, and one study 21 additionally examined school re-opening. All studies used data from national Government sources or international data repositories, and reported on the first half of 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Compared with the usual ARIMA (auto regressive integrated moving average) time series model, the Bayesian inference-based approach produced more accurate forecasts, which is a prerequisite for timely action and planning of epidemic control strategies. Iwata et al ( 8 ) focused on the impact of school closures on mitigating the spread of the coronavirus in Japan. For this purpose, they performed a time series analysis with Bayesian statistics and found that school closures did not reduce the incidence of infection.…”
Section: Bayesian Statistics In Modeling the Spread Of Covid-19mentioning
confidence: 99%